Association between pacifier use and breast-feeding, sudden infant death syndrome, infection and dental malocclusion - Kendall, Garth; Callaghan, A.; Lock, C.; Mahoney, A.; Payne, J.; Verrier, L. (Blackwell Publishing Asia, 2005)
Objective: To critically review all literature related to the association between pacifier use and breastfeeding, Sudden Infant Death Syndrome (SIDS), infection, and dental malocclusion.Background: Knowledge of the health and developmental consequences of pacifier use is important for parents and health professionals. Cursory review of the literature indicates that the use of a pacifier leads to negative outcomes, such as a shortened duration of breastfeeding, infection, and dental malocclusion. Conversely, pacifier use is associated with a reduced incidence of Sudden Infant Death Syndrome (SIDS). A closer examination of the literature reveals important methodological issues that cast doubt on the veracity of some findings. In the absence of a definitive answer, parents need clear information on which they can base child care decisions and health professionals need to be aware of the research evidence upon which they base their practice.Method: The review comprised published and unpublished research literature. The search was restricted to reports published in English, Spanish, and German. The time period covered research published from January, 1960 to October, 2003. A protocol developed by New Zealand Health Technology Assessment was used to guide the search process. The search comprised bibliographic databases, citation searching, other evidence-based and guidelines sites, government documents, books and reports, professional websites, national associations, hand search, contacting national/international experts, and general internet searching. Only randomised controlled trials, prospective cohort studies and, in the case of SIDS research, case-control studies were included. Purely descriptive and cross-sectional studies were excluded, as were qualitative studies and all other forms of evidence. Studies that did not meet the requirement of appropriate temporal sequencing of events and studies that did not present an estimate of the strength of association were not included in the final review.Results: Only one out of a total of ten studies did not report a negative association between pacifier use and breastfeeding duration or exclusivity. Results indicate an increase in risk for a reduced overall duration of breastfeeding from twenty per cent to almost three fold. The data suggest that very infrequent use may not have any overall negative impact on breastfeeding outcomes. With regard to SIDS, all six studies found significantly fewer SIDS cases used a pacifier compared with controls. That is, pacifier use was associated with a reduced incidence of SIDS. These results indicate that the risk of SIDS for infants who did not use a pacifier in the last or reference sleep was at least twice, and possibly five times, that of infants who did use a pacifier. With regard to the association between pacifier use and infection and dental malocclusion it was found that, due to the paucity of epidemiological studies, no meaningful conclusion can be drawn.Implications for practice: Because breast feeding confers an important advantage on all children and the incidence of SIDS is very low, it is recommended that health professionals generally advise parents against pacifier use, while taking into account individual circumstances.